DECONCTRUCTION OF SHARIA BANKING TO PROMOTE INNER BUSINESS EMPLOYMENT SECTOR - Muhlis, Muhlis (Jurnal Iqtisaduna, 2019)
The purpose of this paper is to determine the deconstruction of the role Islamic banks in the SMEs sector in order berkemajuan stretching the domino effect on employment. In order to facilitate the systematic writing of this journal using the literature review methodology . The results of this paper's study show that the effort to advance SMEs is very necessary, seeing the potential and role that is very urgent for our nation, especially related to the absorption of labor that is able to contribute the most to the Indonesian national economy. The more moldy effort, the more labor intensive, thus will reduce unemployment which is a major challenge for the country. SMEs must continue to be encouraged with full support from the government.In conducting and developing its business, it is crowded with entrepreneurs who need capital access support in order to maintain the suistainable of their business. The function of Islamicbanks for SMEs is very much needed as an intermediary institution that collects public funds and channels them back in the form of financing products with various contracts that are in accordance with the provisions of Islamic law.